2010
DOI: 10.1111/j.1528-1167.2010.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adverse effects of antiepileptic drugs, number of coprescribed drugs, and drug load in a large cohort of consecutive patients with drug‐refractory epilepsy

Abstract: SUMMARYPurpose: To evaluate the adverse effects (AEs) of antiepileptic drugs (AEDs) in adults with refractory epilepsy and their relationship with number of coprescribed AEDs and AED load. Methods: Patients with refractory epilepsy were enrolled consecutively at 11 tertiary referral centers. AEs were assessed through unstructured interview and the Adverse Event Profile (AEP) questionnaire. AED loads were calculated as the sum of prescribed daily dose (PDD)/defined daily dose (DDD) ratios for each coprescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
92
1
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 39 publications
17
92
1
15
Order By: Relevance
“…Mechanical manipulation of the thrombus with the guidewire increases the amount of clot that might be impacted by the thrombolytic agent, potentially reducing the amount of fibrinolytic agent used. 61,113,131,150,170,188,192,[195][196][197][198][199][200][201][202][203][204][205] In a retrospective multicenter study of CVT in the United States, 27 (15%) of 182 patients received endovascular thrombolysis. Ten patients were receiving concomitant anticoagulation therapy.…”
Section: Direct Catheter Thrombolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical manipulation of the thrombus with the guidewire increases the amount of clot that might be impacted by the thrombolytic agent, potentially reducing the amount of fibrinolytic agent used. 61,113,131,150,170,188,192,[195][196][197][198][199][200][201][202][203][204][205] In a retrospective multicenter study of CVT in the United States, 27 (15%) of 182 patients received endovascular thrombolysis. Ten patients were receiving concomitant anticoagulation therapy.…”
Section: Direct Catheter Thrombolysismentioning
confidence: 99%
“…196,197,209 A few studies have reported the occurrence and characteristics of patients with seizures accompanying CVT. Among 91 patients, 1 study 218 reported that 32% presented with seizures and 2% developed them during hospitalization; only 9.5% developed late seizures, and seizures were not a predictor of prognosis at 1 year.…”
Section: Saposnik Et Al Diagnosis and Management Of Cerebral Venous Tmentioning
confidence: 99%
“…A literatura apresenta divergências sobre esta questão (DECKERS et al, 2001;CANEVINI et al, 2010;SILLS, 2011;STEPHEN;. Frente a isso a avaliação da possível associação entre a PDD/DDD total ("drug load") e a presença de eventos adversos torna-se um parâmetro prático e útil para a tomada de decisão durante a definição do plano farmacoterapêutico.…”
Section: Os Eventos Adversos E a Relação Pdd/ddd Total ("Drug Load")unclassified
“…В исследовании M. Canevini, были изучены взаимоот-ношения между выраженностью НЯ ПЭП, количеством назначаемых ПЭП и лекарственной нагрузкой ПЭП у па-циентов с фармакорезистентной эпилепсией [75]. Уста-новлено отсутствие значимых различий по выраженности НЯ при использовании режимов моно-и политерапии, количества используемых ПЭП (лекарственная нагрузка).…”
Section: вероятность эффективности терапии при первой неудачеunclassified
“…С помощью линейного мультивариантного регрессион-ного анализа авторами было показано, что число НЯ вследствие ПЭП значимо связано с женским полом (p=0,02) и высоким уровнем депрессии (p<0,0001). Не бы-ло выявлено влияния возраста, типа эпилептического синдрома, частоты приступов, применения режимов мо-но-или политерапии, доз применяемых ПЭП на выра-женность НЯ [75].…”
Section: вероятность эффективности терапии при первой неудачеunclassified